The Commanding Heights: The Battle Between Government and The Marketplace that is Remaking the Modern World - Yergin, Daniel and Stanislaw, Joseph (Simon & Schuster Inc., 1998)
The Commanding Heights shows how a revolution in ideas is transforming the world economy - why it is happening, how it can go wrong and what it will mean for the global economy going into the twenty-first century.
Keywords: Economic policy; Markets; Non-Fiction; Privatization